The Role of Microglia in the Spread of Tau: Relevance for Tauopathies - Perea, Juan R.; Llorens-Martín, María; Ávila, Jesús; Bolós, Marta (Frontiers in Cellular Neuroscience, 2018)
Tauopathies are neurodegenerative diseases which course with the accumulation of Tau, mainly in neurons. In addition, Tau accumulates in a hyperphosphorylated and aggregated form. This protein is released into the extracellular space and spreads following a stereotypical pattern, inducing the development of the disease through connected regions of the brain. Microglia—the macrophages of the brain—are involved in maintaining brain homeostasis. They perform a variety of functions related to the surveillance and clearance of pathological proteins, among other dead cells and debris, from the extracellular space that could compromise brain equilibrium. This review focuses on the role played by microglia in tauopathies, specifically in Alzheimer´s disease, and how the uncoupling of activation/phagocytosis functions can have fatal consequences leading to the development of the pathology.